Antibacterial Efficacy of Citrullus lanatus (Watermelon) Seeds Extracts against Wound Infecting Staphyloccocus aureus and Pseudomonas Aeruginosa - Musa, B.; Shimfuo, B. Y.; Muhammad, J.; Bako, G. D.; Sanusi, S. B. (UMYU Journal of Microbiology Research, 2025)
Watermelon seeds, originally from vine plants, are rich in nutrients and bioactive compounds.  This study aimed to assess the antibacterial efficacy of Citrullus lanatus (Watermelon) seed extracts against wound-infecting Staphylococcus aureus and Pseudomonas aeruginosa.  Preliminary phytochemical screening of the ethanol and aqueous extracts of the watermelon seed was carried out using standard analytical methods.  The two extracts were screened for antibacterial activity against S. aureus and P. aeruginosa, isolated from wound swabs, using both agar well diffusion and broth dilution assays.  The result of the phytochemical screening revealed the presence of saponins, steroids, tannins, phenols, quinones, and terpenoids in the ethanol extract, while saponins, steroids, quinones, phenols, terpenoids, and tannins were present in the aqueous extract.  The inhibitory zone of the ethanol extract against S. aureus ranged between 12.25±3.18 mm to 15.50±0.71 mm, while that of P. aeruginosa ranged between 12.80±0.00 mm to 15.25±1.06 mm at 50 and 100 (mg/mL), respectively.  The inhibitory zone of the aqueous extract against the clinical isolate of S. aureus ranged between 11.50±0.71 mm to 11.75±2.87 mm at 50 and 100 (mg/mL), respectively, while P.  aeruginosa exhibited inhibitory activity of 14.40±0.00 mm at a concentration of 100 mg/mL only.  The Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC), on average, were 50 mg/mL and 100 mg/mL, respectively.  The observed inhibitory activity of the ethanol and aqueous extracts of the seed against the clinical isolates could be due to the presence of phytochemical components within the seed.